2016
DOI: 10.1177/0271678x16667525
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolic alterations in mice subjected to postnatal traumatic stress and in their offspring

Abstract: Adverse environmental and social conditions early in life have a strong impact on health. They are major risk factors for mental diseases in adulthood and, in some cases, their effects can be transmitted across generations. The consequences of detrimental stress conditions on brain metabolism across generations are not well known. Using high-field (14.1 T) magnetic resonance spectroscopy, we investigated the neurochemical profile of adult male mice exposed to traumatic stress in early postnatal life and of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Mice allocated to be reared in isolation and group originated from 20 and 17 litters respectively. Sample size estimation was based on previous experiments (Duarte et al 2012a;Corcoba et al 2016;Gapp et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Mice allocated to be reared in isolation and group originated from 20 and 17 litters respectively. Sample size estimation was based on previous experiments (Duarte et al 2012a;Corcoba et al 2016;Gapp et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the biological factors involved, we recapitulated heritable behavioural and metabolic effects of postnatal trauma across several generations using a previously established model of unpredictable maternal separation combined with unpredictable maternal stress (MSUS) in the mouse, that shows symptoms through up to three generations ( Fig. 1) [2,[4][5][6][7][8][9][10]. We have shown that such postnatal trauma alters small RNA in sperm and that injection of total sperm RNA from exposed male mice into naïve fertilized oocytes elicits symptoms reminiscent of those observed in natural offspring of exposed fathers [2].…”
Section: Introductionmentioning
confidence: 99%
“…To examine the biological factors involved, we recapitulated heritable behavioural and metabolic effects of postnatal trauma across several generations using a previously established model of unpredictable maternal separation combined with unpredictable maternal stress (MSUS) in the mouse, that shows symptoms through up to three generations (Fig. 1) 2,713 . We have shown that such postnatal trauma alters small RNA in sperm and that injection of total sperm RNA from exposed male mice into naïve fertilized oocytes elicits symptoms reminiscent of those observed in natural offspring of exposed fathers 2 .…”
Section: Introductionmentioning
confidence: 99%